Smart and Responsive Drug Delivery Systemsfor Diabetic Ulcers: Advances in Pharmaceutical Design - Shihab, Baraa Mahmood; Almajidi, Yasir Qasim (Journal of Pharmacology and Drug Development, 2025)
Diabetic ulcer is a significant medical issue affecting millions of patients globally due to consequential morbidity, mortality, and health care system costs. The complex pathophysiological process of delayed wound healing in diabetic patients remains inadequately addressed with conventional treatment modalities. This review summarises recent advances in smart, responsive engineered drug delivery systems for the treatment of diabetic ulcers. Moreover, we exemplify these strategies using emerging technologies, including nanotechnology, hydrogel matrices, stimulus-responsive systems, and bioactives. New methodologies, including next-generation approaches such as 3D-printed scaffolds, nanofiber systems, and theranostic platforms, are presented as alternative treatment options that could change the landscape of diabetes-related wound care. Discussions on the challenges of translation, regulation, and application of new pharma-technologies in clinical research are offered